2008
DOI: 10.1371/journal.pone.0004068
|View full text |Cite
|
Sign up to set email alerts
|

Mild Electrical Stimulation with Heat Shock Ameliorates Insulin Resistance via Enhanced Insulin Signaling

Abstract: Low-intensity electrical current (or mild electrical stimulation; MES) influences signal transduction and activates phosphatidylinositol-3 kinase (PI3K)/Akt pathway. Because insulin resistance is characterized by a marked reduction in insulin-stimulated PI3K-mediated activation of Akt, we asked whether MES could increase Akt phosphorylation and ameliorate insulin resistance. In addition, it was also previously reported that heat shock protein 72 (Hsp72) alleviates hyperglycemia. Thus, we applied MES in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(142 citation statements)
references
References 51 publications
(66 reference statements)
10
132
0
Order By: Relevance
“…The intra-articular temperature was sufficiently raised by direct heat conduction using electrodes made of special rubber that conducts electricity and emits heat. In addition, we previously confirmed that MES þ HS treatment (10 min per session; twice/week for 16 weeks) had no observable adverse effects in mice, 16 and that MES did not induce cell toxicity in vitro.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The intra-articular temperature was sufficiently raised by direct heat conduction using electrodes made of special rubber that conducts electricity and emits heat. In addition, we previously confirmed that MES þ HS treatment (10 min per session; twice/week for 16 weeks) had no observable adverse effects in mice, 16 and that MES did not induce cell toxicity in vitro.…”
Section: Discussionsupporting
confidence: 54%
“…1A). 16 The electrodes were connected to a BioMetronome TM (Tsuchiya Gum Co., Ltd., Kumamoto, Japan), that can apply MES. Electrical stimulation for cells was delivered using 5 V (55 pulses per second [pps]) of direct current with individual pulse duration of 0.1 ms.…”
Section: Chondrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…HSPs act as molecular chaperones, and the expression can increase in response to physical and chemical stressors as well as oxidative stress. Several laboratories (21,35) have demonstrated that induction of HSPs by heat treatment can protect against obesity-related insulin resistance and that an increased expression of HSP70 and HSP25 plays a significant role in protecting SM from the development of age-related insulin resistance (20). Moreover, the small HSPs especially protect against ROS and stress situations such as ATP depletion (1).…”
Section: E500mentioning
confidence: 99%
“…Gupte et al showed that a heat treatment improved glucose tolerance and insulin resistance in high-fat-fed rats [9]. We have shown that a combination of heat shock treatment (HS) and mild electrical stimulation (MES) [42°C pads and 12-V direct current (55 pulses/s with 0.1-ms duration) for 10 min, twice per week] could effectively induce HSP72 mRNA and protein in high-fat-fed mice, which resulted in improved insulin signaling and glycemic control with decreased visceral fat [10]. In this method, MES (12-V direct current, 55 pulses/s with 0.1-ms duration) enhances heat induction of HSP72 at least in part by a suppression of HSP72 degradation [11] and may also activate insulin signaling by modulating the membrane localization of the insulin receptor [12].…”
Section: Increased Expression Of Hsp72 Ameliorates Insulin Resistancementioning
confidence: 99%